(untitled) (Investigación y Desarrollo, 2022)
Alterations in the immune system are often found in children with Autism Spectrum Disorders [ASD], leading to an aberrant immune response which compromises host defense. Fewer regulatory T-cells, elevation in inflammatory cells and proinflammatory cytokines have been highly reported in this population and it has been recently seen as a chronic neuroinflammatory disorder. Cytokines are often dysregulated in ASD especially IL-6, which is one of the biggest concerns during the current COVID-19 pandemic, as well as other immune dysregulations. We strongly believe that this proinflammatory environment in ASD could increase the vulnerability of a poor clinical outcome for COVID-19 infection.